The Microstructure and Properties of an Al-Mg-0.3Sc Alloy Deposited by Wire Arc Additive Manufacturing - Lingling Ren; Huimin Gu; Wei Wang; Shuai Wang; Chengde Li; Zhenbiao Wang; Yuchun Zhai; Peihua Ma (Metals, 2020)
Al-Mg alloys can reach medium strength without a solid solution and quenching treatment, thereby avoiding product distortion caused by quenching, which has attracted the attention of wire arc additive manufacturing (WAAM) researchers. However, the mechanical properties of the WAAM Al-Mg alloy deposits obtained so far are poor. Herein, we describe the preparation of Al-Mg-0.3Sc alloy deposits by WAAM and detail the pores, microstructure, and mechanical properties of the alloy produced in this manner. The results showed that the number and sizes of the pores in WAAM Al-Mg-0.3Sc alloy deposits were equivalent to those in Al-Mg alloy deposits without Sc. The rapid cooling characteristics of the WAAM process make the precipitation morphology, size, and distribution of the primary and secondary Al3Sc phases unique and effectively improve the mechanical properties of the deposit. A primary Al3Sc phase less than 3 μm in size was found to precipitate from the WAAM Al-Mg-0.3Sc alloy deposits. The primary Al3Sc phase refines grains, changes the segregated β(Mg2Al3) phase morphology, and ensures that the mechanical properties of horizontal and vertical samples of the deposits are uniform. After heat treatment at 350 °C for 1 h, the WAAM Al-Mg-0.3Sc alloy deposits precipitated a secondary Al3Sc phase, which was spherical (diameter about 20 nm) and had high dispersity. This phase blocks dislocations and subgrain boundaries, causes a noticeable strengthening effect, and further improves the mechanical properties of the deposits, up to a horizontal samples tensile strength of 415 MPa, a yield strength of 279 MPa, and an elongation of 18.5%, a vertical samples tensile strength of 411 MPa, a yield strength of 279 MPa, and an elongation of 14.5%. This Al-Mg-Sc alloy is expected to be widely used in the WAAM field.